CTL-Derived Granzyme B Participates in Hippocampal Neuronal Apoptosis Induced by Cardiac Arrest and Resuscitation in Rats - Ji, Ning-Ning; Wu, Liang; Shao, Bo-Ming; Meng, Qing-Xiang; Xu, Jin-Nan; Zhu, Hao-Wen; Zhang, Yong-Mei (Frontiers in Neurology, 2019)
Hippocampal neuronal apoptosis is a devastating consequence of cardiac arrest (CA) and subsequent cardiopulmonary resuscitation (CPR). In this study, we assessed the contribution of cytotoxic T lymphocyte (CTL)-derived toxic mediator granzyme B (Gra-b) to the hippocampal neuronal apoptosis following CA/CPR in rats. Rats that experienced CA/CPA presented with cytosomal shrinkage, dense cytoplasm, and intensive eosinophilic staining in the CA1 region of dorsal hippocampus. CA/CPR rats also exhibited inability in spatial navigation and a local infiltration of peripheral CD8+ T cells into the hippocampus. The protein levels of Gra-b, cleaved Caspase-3, and cleaved PARP1 were significantly elevated in rats undergoing CA/CPR. Pretreatment with Gra-b inhibitor suppressed Gra-b release, attenuated hippocampal neuronal apoptosis, as well as improved cognitive impairment. Together, this study indicates that CTL-derived Gra-b is involved in the CA/CPR-induced neuronal apoptosis, and pharmacological manipulation of Gra-b may represent a novel avenue for the treatment of brain injury following CA/CPR.